2021
DOI: 10.1002/1348-9585.12283
|View full text |Cite
|
Sign up to set email alerts
|

Association of teleworking and smoking behavior of U.S. wage and salary workers

Abstract: Introduction The COVID‐19 pandemic has led to a major shift in workspace from office to home. This report examined how telecommuting is related to smoking behavior of wage and salary workers. Methods Self‐reported smoking behavior of 1,390 U.S. wage and salary workers aged 16–64 years from the Tobacco Use Supplement of the Current Population Survey 2018/19 were linked to the 2018 American Time Use Survey. Weighted multivariate logistic regression predicting smoking prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…There are concerns amongst public health professionals about the misinterpretation of the claims as reduced harm ( East et al, 2021 , Popova et al, 2018 , Zou et al, 2021 ) and a potential increase in youth uptake ( Jeong et al, 2019 ). This authorization occurred during the COVID-19 pandemic, when health risks from infection with COVID-19 in smokers were highlighted ( Giovenco et al, 2021 , Nargis et al, 2021 ). Some studies have reported a reduction in smoking as a result of greater risk perception due to COVID-19 ( Rigotti et al, 2021 , White, 2021 , Gravely, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are concerns amongst public health professionals about the misinterpretation of the claims as reduced harm ( East et al, 2021 , Popova et al, 2018 , Zou et al, 2021 ) and a potential increase in youth uptake ( Jeong et al, 2019 ). This authorization occurred during the COVID-19 pandemic, when health risks from infection with COVID-19 in smokers were highlighted ( Giovenco et al, 2021 , Nargis et al, 2021 ). Some studies have reported a reduction in smoking as a result of greater risk perception due to COVID-19 ( Rigotti et al, 2021 , White, 2021 , Gravely, 2021 ).…”
Section: Introductionmentioning
confidence: 99%